Aplikasi Metode Aktivasi Secara Kimia Pada Zeolit Alam Sebagai Penjerap Logam dalam Proses Pemurnian Air - Puput Eka Suryani (SIMETRIS, 2019)
Population growth that continues to increase every year has an effect on the increasing need for clean water to meet daily life. The availability of water sources that continue to run out due to being displaced by the human population every year needs serious attention. This is because the need for water covers almost all sectors of human life such as industry, tourism, agriculture, households, etc. Basically water quality can be influenced by several things such as environmental pollution, mineral content in water, and the presence of dissolved metals due to the distribution process. An increase in population is followed by an increase in some human activities that can cause water pollution. The high level of environmental pollution due to industrial waste results in a decrease in the quality of the springs. Indonesia is one of the countries that has abundant natural zeolite sources. The use of zeolites can be optimized as a solution in cases of water pollution or water quality improvement. In this research, we will study further about the ability of chemically activated natural zeolite to adsorb heavy metals in water. The sample water used in this study was taken from groundwater in the Cepu area which is predicted to have a high level of hardness. Natural zeolite was activated by acid using 2 M HCl solution. The structure of zeolite was analyzed using X-Ray Difraction (XRD), while the adsorption ability was analyzed using Atomic Absorption Spectroscopy (AAS). The results showed that the main mineral constituent of the natural zeolite used was modernite. Chemical activation is able to increase the active site in natural zeolite, it can be seen from the appearance of higher peaks in the modified zeolite.